Taguchi method to improve the production of sugar-rich hydrolysate from non-delipidated spent coffee grounds, and subsequent recovery of lipids and bioactive compounds. Issue 2 (4th March 2019) - Go, Alchris Woo; Conag, Angelique Trugillo; Bertumen, Ma. Mitzi N.
ABSTRACT: The direct hydrolysis of non-delipidated SCG was investigated in this study to assess the potential of the direct utilization of wet SCG and recovery of the available lipids. An optimum sugar yield was achieved using 4% v/v sulfuric acid at an SSR of 8 mL/g for a hydrolysis time of 3 to 4 hours at 95 °C. A sugar recovery of 81 to 98% of the available sugars was achieved. Hydrolysates contain ∼40 g/L of reducing sugars and 4.7 g/L of protein, while inhibitor concentrations were found to be below inhibitory limits. Around 67% of the solid was recovered as residue having a lipid content of ∼27% (∼103% recovery). Furthermore, an increase in the ethanol extractables was observed and found to be ∼11%, containing ∼21% of polyphenols in gallic acid equivalent. Moreover, this approach allows a potential energy savings of as much as ∼48% when compared to conventional approaches. Lipids remained intact in the solid residue with structural lipids released during direct hydrolysis of non-delipidated SCG, thereby resulting in a lipid recovery beyond 100%. The presence of lipids does not hinder the recovery of the available sugars. Direct utilization of non-delipidated SCG potentially reduces the energy requirements during processing and facilitates recovery of bioactive components.